Fish mouth diversion for sediment control in the Ningxia Qixing canal of the yellow river: A hydrodynamic and sediment transport modeling study - Suiju Lv; Mingyang Liu (Alexandria Engineering Journal)
In addressing sediment accumulation challenges in the water diversion canal and enhancing both water utilization and ecological conditions, this study introduces a fish mouth engineering design, akin to the sediment reduction strategies used at the Dujiangyan water conservancy hub. A specialized two-dimensional hydrodynamic and sediment transport model was developed, specifically tailored to the Qixing Canal section in Ningxia. Utilizing SMS software, an unstructured grid division of the study area was executed. The research employed simulations under two distinct scenarios: direct water diversion and fish mouth engineering at the canal head. These simulations were pivotal in analyzing the variations in sedimentation thickness and sediment concentration across different flow rates and irrigation cycles. It was observed that the use of the fish mouth engineering for water diversion significantly improved the sedimentation thickness, underscores the efficacy of the fish mouth model in altering the structural characteristics of water flow and achieving a redistribution of water flow and sediment within the canal. This approach to fish mouth diversion and sediment reduction substantially curtails sediment accumulation in the irrigation canal, presenting a viable strategy for canal head design in the self-flow irrigation areas of the Yellow River. This research result provides certain reference value for water conservancy engineering organizations.